1976
DOI: 10.1136/oem.33.3.166
|View full text |Cite
|
Sign up to set email alerts
|

Byssinosis: a follow-up study of cotton ginnery workers in the Sudan.

Abstract: A follow-up study of lung function tests and dust measurements was undertaken in ginnery workers employed in five ginning factories. Respiratory symptoms and respiratory function tests (FEV1 and FVC) were first recorded in 1967 on a total of 382 workers (323 permanently employed ginnery workers, 35 seasonal farfara workers, and 24 fire brigade men as controls). In 1969 after a six-month break from ginning before the start of the season, a follow-up study of lung function tests was undertaken on 96% of the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…We did not compare this with their prevalence in a control group so we cannot say whether sisal dust played a part in the pathogenesis of chronic bronchitis. The low prevalence of chronic cough and chronic bronchitis is comparable to that in Sudanese ginnery workers (Khogali, 1976) and can be explained in these African workers similarly by their moderate smoking habits, as 900% of workers in both series smoked less than 10 cigarettes/day, and also by the low atmospheric pollution outside the factories.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We did not compare this with their prevalence in a control group so we cannot say whether sisal dust played a part in the pathogenesis of chronic bronchitis. The low prevalence of chronic cough and chronic bronchitis is comparable to that in Sudanese ginnery workers (Khogali, 1976) and can be explained in these African workers similarly by their moderate smoking habits, as 900% of workers in both series smoked less than 10 cigarettes/day, and also by the low atmospheric pollution outside the factories.…”
Section: Discussionmentioning
confidence: 71%
“…As the mean duration of exposure is significantly higher in brushing compared with that in spinning (Table 1), it may be assumed that the time-weighted dust measurement is far greater in brushing compared with that in spinning. This measurement was found to be highly correlated with the prevalence of byssinosis in cotton workers (Fox et al, 1973;Khogali, 1976).…”
Section: Discussionmentioning
confidence: 82%
“…Khogali (1969) recorded histories of chest tightness (after annual holiday) in 20% of ginnery and 48% of farfara workers in the Sudan. Two years later, Khogali (1976) found that the same workers showed a mean FEVY increase; dust levels and prevalences of respiratory symptoms remained high. El Batawi (1962) found that symptoms of byssinosis were actually more prevalent in ginning (38%) and bale pressing (53%) than in carding (27%), although the last operation had a higher proportion with grade II byssinosis.…”
Section: Discussionmentioning
confidence: 95%
“…9,10 In our study we have observed that all the workers suffering from one or other type of respiratory disorders are smokers. None of the non-smoker worker suffered from any type of respiratory disorders.…”
Section: Discussionmentioning
confidence: 78%